2023
DOI: 10.3390/molecules28031351
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Repellent Activity of Plant Essential Oils against Dengue Vector, Aedes aegypti

Abstract: Repellents are effective personal protective means against outdoor biting mosquitoes. Repellent formulations composed of EOs are finding increased popularity among consumers. In this study, after an initial screening of 11 essential oils (EOs) at the concentration of 33 μg/cm2, five of the most repellent EOs, Perovskia atriplicifolia, Citrus reticulata (fruit peels), C. reticulata (leaves), Mentha longifolia, and Dysphania ambrosioides were further investigated for repellent activity against Aedes aegypti mosq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…Similar to the insecticidal activity, Z. officinale extract displayed the strongest repellent effect, deterring S. oryzae to a greater extent than other extracts. This finding supports previous studies reporting the repellent properties of ginger against various insect pests (Edris et al, 2016;Haris et al, 2023). The repellent activity could be attributed to the volatile compounds present in the extract, which S. oryzae finds aversive and avoids.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the insecticidal activity, Z. officinale extract displayed the strongest repellent effect, deterring S. oryzae to a greater extent than other extracts. This finding supports previous studies reporting the repellent properties of ginger against various insect pests (Edris et al, 2016;Haris et al, 2023). The repellent activity could be attributed to the volatile compounds present in the extract, which S. oryzae finds aversive and avoids.…”
Section: Discussionsupporting
confidence: 91%
“…scoparia essential oils was investigated against adult female Ae. aegypti by using the human bait method, as previously described [ 43 ]. One and ten percent solutions of an essential oil prepared in ethanol were used to test the repellency against Ae.…”
Section: Methodsmentioning
confidence: 99%
“…The repellent activity of the extracted A. scoparia essential oils was investigated against adult female Ae. aegypti by using the human bait method, as previously described [43].…”
Section: Mosquito Repellency Bioassaymentioning
confidence: 99%
“…Similarly, a previous study reported that β-caryophyllene and nerolidol showed some repellency towards female Ae. aegypti when tested individually, whereas the combination of β-caryophyllene and nerolidol exhibited an excellent mosquito-repellent activity for an extended period of time [ 20 ]. To our knowledge, very few studies have described the mosquito-repellent activity of the L. camara EO or extracts.…”
Section: Discussionmentioning
confidence: 99%